Intravenous acyclovir causing vesicular eruptions at and away from infusion site in a child - Nauriyal, Deepty; Shukla, Anand (International Journal of Contemporary Pediatrics, 2023)
Acyclovir is an antiviral drug used to treat infections caused by Herpes virus. Acyclovir is known to cause systemic and local adverse reactions. Local adverse reactions include inflammatory reactions at infusion site. We case report a child with vesicular eruptions at and away from infusion site due to IV acyclovir. It is quite a rare finding, as only few such cases have been reported till now in literature.